Photoluminescence Quenching and Structure of Nanocomposite Based on Graphene Oxide Layers Decorated with Nanostructured Porphyrin - Omar Bajjou; Precious Nametso Mongwaketsi; Mohammed Khenfouch; Anass Bakour; Mimouna Baïtoul; Malik Maaza; Jany Wery Venturini (Nanomaterials and Nanotechnology)
Nanocomposites based on few-layers graphene oxide (FGO) decorated with porphyrin nanorods (PN) were synthesized and the interfacial interaction between these two components was investigated by using scanning electron microscopy (SEM), photoluminescence spectro‐ scopy, resonant Raman scattering and Fourier transform infrared (FT-IR) techniques. SEM showed good exfoliation of FGO and its successful interaction with the PN. The photoluminescence results showed an important interac‐ tion between FGO and PN resulting in a quenching of the photoluminescence of the PN-FGO composite. Resonant Raman with PN aggregates and FT-IR results revealed a π- π intermolecular interaction confirming the energy/charge transfer. Moreover, the investigation of X-ray diffraction confirmed the intercalation of PN in FGO and their disaggregation. The findings presented here are an impor‐ tant contribution to achieving the functionalization of graphene derivative surfaces with PN for various optoe‐ lectronic applications and particularly photovoltaic cells.